Race and Sex Differences in Intelligence and Personality: A Tribute to Richard Lynn at Eighty - Nyborg, Helmuth (2013)
This special issue commemorates Richard Lynn's work on individual differences on his eighty-second birthday, which took place on the twentieth of February, 2012. Richard Lynn has a long association with Personality and Individual Differences. This special issue consists of critical evaluations of Richard Lynn's work on national and racial differences in intelligence and personality, the effects of national IQs and economic development and a number of sociological, demographic and epidemiological phenomena, the Lynn-Flynn effect, sex differences in intelligence and specific abilities, eugenics and dysgenics, and the intelligence of the Jews.
Članci sadržani u ovoj knjizi prvo su bili objavljeni u Personality and Individual Differences, Vol.53(2), Jul 2012, str.75-162. i ponovno su objavljeni uz dozvolu Elsevier BV.
Bibliografija na kraju svakog poglavlja.
Kazalo
Keywords: Richard Lynn; opća inteligencija; rasa; razlike između spolova; inteligencija; ličnost; nacionalne razlike; Standardne progresivne matrice -- Libija; WAISS-III; Flynn efekt; Lynn-Flynn efekt